Evans, Ruth i Holt, Louise (eds.) (2014). Diverse spaces of childhood and youth: gender and other socio-cultural differences - Luque Garrofé, Montse (Documents d'Anàlisi Geogràfica, 2015)
Evans, Ruth i Holt, Louise (eds.) (2014) Diverse spaces of childhood and youth: gender and other socio-cultural differences Oxon: Routledge, 208 p. ISBN 978-0-415-83437-7